Planetary Mass Spectrometry for Agnostic Life Detection in the Solar System - Chou, Luoth; Mahaffy, Paul; Trainer, Melissa; Eigenbrode, Jennifer; Arevalo, Ricardo; Brinckerhoff, William; Getty, Stephanie; Grefenstette, Natalie; Da Poian, Victoria; Fricke, G. Matthew; Kempes, Christopher P.; Marlow, Jeffrey; et al. (Frontiers in Astronomy and Space Sciences, 2021)
For the past fifty years of space exploration, mass spectrometry has provided unique chemical and physical insights on the characteristics of other planetary bodies in the Solar System. A variety of mass spectrometer types, including quadrupole, magnetic sector, time-of-flight, and ion trap, have and will continue to deepen our understanding of the formation and evolution of exploration targets like the surfaces and atmospheres of planets and their moons. An important impetus for the continuing exploration of Mars, Europa, Enceladus, Titan, and Venus involves assessing the habitability of solar system bodies and, ultimately, the search for life--a monumental effort that can be advanced by mass spectrometry. Modern flight-capable mass spectrometers, in combination with various sample processing, separation, and ionization techniques also enable sensitive detection of chemical biosignatures. While our canonical knowledge of biosignatures is rooted in Terran-based examples, agnostic approaches in astrobiology can cast a wider net, to search for signs of life that may not be based on Terran-like biochemistry. Here, we delve into the search for extraterrestrial chemical and morphological biosignatures and examine several possible approaches to agnostic life-detection using mass spectrometry. We discuss how future missions can help ensure that our search strategies are inclusive of unfamiliar life forms.